PERAN PEMUDA DALAM PELESTARIAN SENI TRADISIONAL BENJANG GUNA MENINGKATKAN KETAHANAN BUDAYA DAERAH (Studi Di Kecamatan Ujungberung Kota Bandung Provinsi Jawa Barat) - Mantri, Yaya Mulya (Jurnal Ketahanan Nasional, 2014)
The role of young man in preservation Benjangâs folk art was assessed as fair which included five roles which were: the role of endowment, the role of owner, the role of doer, the role of innovative, and role of educative. Young man faced fi ve constraints in Benjangâs folk art preservation, that was first of lack of fund in developing Benjangâs folk art, second lack of government involvement in Benjangâs folk art development, third there was no involvement of academician side in Benjangâs management management and folk art show packaging, fourth lack of understanding of artistic aesthetics the Benjangâs actors, and fifth the entry of foreign culture in massif. Implication to cultural resilience of area: increasing cultural awareness and identity of area, change without trespassing cultural originality of area, and penetrating cultural warded of strangers foreigners which unmatched to area culture.Keywords: Benjang, Traditional Art, Cultural Resilience of Area